2005
DOI: 10.1097/00001888-200510001-00012
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence and Clinical Skills: Preliminary Results from a Comprehensive Clinical Performance Examination

Abstract: Various aspects of EI are modestly implicated in students' clinical skills as assessed by standardized patients in an OSCE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
88
4
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(104 citation statements)
references
References 19 publications
5
88
4
7
Order By: Relevance
“…This suggests that empathy is a desirable skill in doctors: more empathic doctors tend to be better in patient-oriented communications skills and not worse in task-oriented skills. A similar result was found by Stratton et al (2005). Because there are indications that empathy is not easily trained, this is valuable information for educators (Stepien & Baernstein 2006;Brunero et al 2010).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…This suggests that empathy is a desirable skill in doctors: more empathic doctors tend to be better in patient-oriented communications skills and not worse in task-oriented skills. A similar result was found by Stratton et al (2005). Because there are indications that empathy is not easily trained, this is valuable information for educators (Stepien & Baernstein 2006;Brunero et al 2010).…”
Section: Discussionsupporting
confidence: 77%
“…The four sub-scales are: Perspective taking (PT), Fantasy (FS), Empathic concern (EC) and Personal distress (PD). In earlier research (Stratton 2005), a relationship between the IRI and clinical skills was found. The sub-scales EC and FS in particular were related to communication skills.…”
Section: Instrumentsmentioning
confidence: 82%
See 1 more Smart Citation
“…15 However, there is limited research that has specifically identified individual differences in personality that might impact technical skills performance in stressful situations like the OSCE.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Using the TMMS and Davis' Interpersonal Reactivity Index (IRI) as measures of EI traits, Stratton and colleagues showed a significant relation between EI and empathy and communication skills. 21 In their study using the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) v2.0 on nurses, Codier and colleagues showed a correlation between clinical staff nursing performance and EI scores. 22 In pharmacy, Romanelli et al discussed EI as a possible predictor of academic and professional success.…”
Section: Introductionmentioning
confidence: 99%